Influence of evidence, time, source and interferents in the observation of biological fluids with forensic lights (2015)
Introduction: The laboratory receives different evidence for analysis, which maycontain fluids such as blood, semen, saliva or urine. A support tool in identifying nonvisible biological stains is observation with forensic lights. At present, there have been research advances in reference to wavelength and combination of different filters for the observation of biological fluids. Methodology: For this research, the alternate lights equipment Polilight® Flare with blue light was used, along with a filter and orange glasses, for observing stains of biological fluids deposited on different types of textiles and other surfaces that are frequently received by the laboratory. Results: The main result of this study was to determine the reliability of this equipment in terms of reproducibility andrepeatability of results, as well as the influence of variables such as substrate, age of the stain, source of fluid, and possible interferents in the observation of biological fluid fluorescence. Conclusions: It was found that biological stains emitting the strongest fluorescence were semen followed by urine and saliva stains. Bloodstains did not emit fluorescence and were referred to as non-fluorescent. Permeability of substrates made fluorescence halo greater, especially on light colors. Moreover, no statistically significant differences were observed in the fluorescence emission of azoospermic semen with respect to normspermic semen.